GOYANG DANGDUT DAN REPRESENTASI IDEOLOGI DI TELEVISI - Agus Rianto (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2013)
As a genre of popular music, dangdut is part of pop culture entertainment industry.Dangdut has a "community of listeners" , in addition to obtaining maintenance andreasonable award. People no longer question of where such music originated and who actsas the source. But in pop culture it is also defined as "the location of the fight" , wheremany of the meanings defined and debated. It is not enough to underestimate the popculture as only serving to the complement of the system in capitalism and patriarchy,allowing it to anesthetize people with false consciousness.Pop culture can also be seen as the location where the contested meanings anddominant ideologies can be disturbed; between the market and the various ideologies;between investors and producers; between director and actor; between publishers andauthors; between capitalists and workers; among women and men; groups of heterosexualand homosexual; groups of blacks and whites; old and young; between what the meaningof all things, and what it means, a battle of control ( towards the meaning) that sustaincontinously. Thus, finally, in the television, dangdut do not only just offer entertainment,but also the ideologies that continue to be produced and reproduced in the name ofentertainment world called dangdut .